The Romanian Public Television– A New Beginning. Proposals and Strategies to Defeat the Crisis - Ion STAVRE (Revista de Management Comparat International)
This article analyses the current situation of the Romanian public television versus other European public television networks. This analysis is complemented by several proposals regarding potential amendments to the functioning law of the Romanian audiovisual field (law 41/1994) and ideas towards a development strategy that would help the public television regain its leading position in the Romanian mass media. The proposals and ideas that are put forward are based and endorsed by the double role of the author, as professor at The National School of Political Science and Public Administration (SNSPA) and producer of several political programs within the public television network (including the first program entirely dedicated to the European Parliament, financed by a grant from the European Parliament).